A A case report of acinar type prostate cancer with urogenital differentiation in a Terrier dog - Tural Çifçi, A; Ateş, MB; Ortatatlı, M; Tuzcu, M (Journal of the Hellenic Veterinary Medical Society, 2026)
In this presentation, a case of cystic adenocarcinoma of the prostate in a 13-year-old Terrier male dog is described pathologically. The patient was brought to the Selcuk University Veterinary Faculty animal hospital with complaints of cross-walking for two months, urinary incontinence and paralysis in the last two days. After the physical examination, the total prostate was removed by mass surgery and brought to the pathology laboratory. Macroscopically, it was observed that the prostate was 4 x 7 x 9 cm in size, red in color, sticky and necrotic. Tissue sections prepared after routine tissue processing procedures were stained with Hematoxylin Eosin (HE) and immunohistochemically (IHC) using PCNA antibody. In microscopic examination; Acinar/tubular structures formed by atypical tumor cells with or without numerous central lumens were determined. It was realized that some tumor cells showed squamous differentiation and contained vacuoles in their cytoplasm. Tumor cells with localized intracytoplasmic eosinophilic bodies (Melamed-Wolinska) were also detected. In some parts of the tumor, epithelial cells embedded in the stroma were seen in the form of "signet ring". In the immunohistochemical staining of prostate sections with PCNA antibody, severe immunoreactivity was observed in tumor cells. As a result of all these, a rare diagnosis of acinar type prostate adenocarcinoma with urogenital differentiation was made.